A Higher Tidal Volume May Be Used for Athletes according to Measured FVC - Pavlos Myrianthefs; George Baltopoulos (The Scientific World Journal)
We investigated whether professional athletes may require higher tidal volume (Tv) during mechanical ventilation hypothesizing that they have significantly higher “normal” lung volumes compared to what was predicted and to nonathletes. Measured and predicted spirometric values were recorded in both athletes and nonathletes using a Spirovit SP-1 spirometer (Schiller, Switzerland). Normal Tv (6 mL/kg of predicted body weight) was calculated as a percentage of measured and predicted forced vital capacity (FVC) and the difference (δ) was used to calculate the additional Tv required using the equation: New Tv(TvN)=Tv+(Tv×δ). Professional athletes had significantly higher FVC compared to what was predicted (by 9% in females and 10% in males) and to nonathletes. They may also require a Tv of 6.6 mL/kg for males and 6.5 mL/kg for females during mechanical ventilation. Nonathletes may require a Tv of 5.8 ± 0.1 mL/kg and 6.3 ± 0.1 mL/kg for males and females, respectively. Our findings show that athletes may require additional Tv of 10% (0.6/6 mL/kg) for males and 8.3% (0.5/6 mL/kg) for females during general anesthesia and critical care which needs to be further investigated and tested.